Pesquisa em linfonodo-sentinela em pacientes com adenocarcinoma de cólon - Antonio Hilario Alves Freitas (2007)
The colorectal cancer is responsible for 8.000 deaths per year in Brazil. It is believed that there is sub staging in the post operative. The objective of this study is to research on the sentinel lymph node in patients with colon cancer through markers (patent blue dye and radioisotopic 99mtechnetium labeled phytate); showing the value of lymphoscintigraphy to confirm the capturing of radioisotopic by the lymph nodes in the surgical process; checking the alterations in the stagingof patients after the exams of sentinel lymph nodes by the routine histology, multilevel section and immunohistochemical. The sample was composed by 18 patients, all of them diagnosed with cancer subjected to: laparotomy, lymphatic mapping with injection of the markers of lymph nodes in the peritumoral subserosa and peroperative identification of the nodes by direct vision of the dye, and capture of radioactivity with gamma probe. All of the lymph nodes were examined with routine pathology done by hematoxilin-eosin stained, and the patients without nodes metastases were added to the examinations with multilevel section and immunohistochemical to the sentinel. Results: the intraoperative identification of sentinel lymph nodes with the marker occurred in 16 (88,8%) of the cases. Considering that 13 patients with marker in sentinel node were lymphoscintigraphy was obtained, 12 (92,4%) of them were identified by images. The global sensitivity of this method was 66,7% and the false negative was 33,3%. After the histological examination with multilevel section and immunohistochemical of 11 patients, one (9%) case of micrometastasis was diagnosed, being considered ultrastaging.Conclusions: It can be said that the procedure is viable, safe and with a high level of success; the association of the markers is benefical, but the radioisotopic is more effective; the lymphoscintigraphy of the surgical specimen is capable of certifying the presence of absorption of the radioisotopic marker by the lymph node; the incidence of lymph node metastasis is, proportionally, the same in the sentinel and non sentinel nodes, therefore, the radical lymphadenectomy must be done in all patients; the techniques of the multilevel section and immunohistochemical contribute to improve the effectiveness of the lymph node metastases diagnose.